Apoptotic cell clearance: basic biology and therapeutic potential - Poon, Ivan K. H. (2014)
Prompt removal of apoptotic cells by phagocytes is important for maintaining tissue homeostasis. The molecular and cellular events that underpin apoptotic cell recognition and uptake, and the subsequent biological responses are increasingly better defined. The detection and disposal of apoptotic cells generally promote an anti-inflammatory response at the tissue level, as well as immunological tolerance. Consequently, defects in apoptotic cell clearance have been linked with a variety of inflammatory diseases and autoimmunity. Conversely, under certain conditions such as killing tumour cells by specific cell death inducers, the recognition of apoptotic tumour cells can promote an immunogenic response and anti-tumour immunity. Here, we review the current understanding of the complex process of apoptotic cell clearance in physiology and pathology, and discuss how this knowledge could be harnessed for new therapeutic strategies.